Placenta Accreta: Inevitable Massive Haemorrhage - Filipe, Catarina; Lugarinho Monteiro, Teresa; Carvalhas, Joana; Mártires, Emília (Journal of the Portuguese Society of Anesthesiology, 2018)
Background: Postpartum haemorrhage is a cause of maternal morbidity and mortality. Placenta accreta is rare and usually associated with placenta praevia. We report a case of postpartum haemorrhage secondary to placenta accreta, occurred in a tertiary maternity hospital. Case Report: Pregnant with advanced maternal age, anaemia and history of three caesarean sections was referred to Obstetrician. Her study revealed placenta praevia, with a suspicion of accretism, and normocytic normochromic anaemia. Although the anaesthetic plan was previously delineated, in the operating room occurred massive haemorrhage ending up in hysterectomy. The massive obstetric haemorrhage protocol was applied, with no more adverse events. Discussion: Successful management of massive obstetric haemorrhage, in both the emergency and elective situation, requires team work. Early identification of risk factors is crucial, as well as the early involvement of senior professionals and the application of the institutional protocol on managing this critical event.